Epidermal growth factor receptor exon 20 insertion variants in non-small cell lung cancer patients. (January 2022) - Malapelle, Umberto; Pilotto, Sara; Reale, Maria Lucia; Passiglia, Francesco; Pisapia, Pasquale; Pepe, Francesco; Belluomini, Lorenzo; Galetta, Domenico; Cortinovis, Diego; Tiseo, Marcello; Passaro, Antonio; Seminati, Davide; et al.
Graphical abstract: Highlights: EGFR exon 20 insertions occur in about 1.5–3.0 % of NSCLC. NGS technology is the best option to detect EGFR exon 20 insertions. Chemotherapy still represents the current standard of care. Promising new EGFR TKIs and bispecific antibodies are under evaluation. Abstract: Epidermal growth factor receptor ( EGFR ) exon 20 insertions occur rarely among different cancer types, with the highest frequency reported among non-small-cell lung cancer (NSCLC) patients, particularly adenocarcinomas (ADCs). Exon 20 insertions fall back in the tyrosine kinase domain, and can be clustered into two principal groups represented by in frame insertions and three to 21 bp (corresponding to 1–7 amino acids) duplications within amino acids 762 and 774. The identification of these alterations is key for an adequate management of NSCLC patients due to the possibility to treat these patients with specific targeted therapies. Next generation sequencing (NGS) technology, able to detect several hotspot gene mutations for different patients simultaneously, is the best detection approach due to its higher sensitivity and specificity compared to other techniques. Here we reviewed the principal biological characteristics, the main detection technologies and treatment options for NSCLC patients harbouring EGFR exon 20 insertions.